Pengaruh Faktor Idiosinkratik Matteo Salvini Dalam Kebijakan Luar Negeri “Salvini Decree” Italia 2018 - Galih Antonius Ola Lewoema; Arisanto, Puguh Toko (International Forum of Researchers and Lecturers, 2024)
This research aims to analyze the influence of Matteo Salvini's idiosyncratic factors in the output of anti-migrant policies, so called Salvini Decree in Italy after the winning of the 2018 general election. According to Matteo Salvini, the migrant issue is a threat to Italy's national identity. The authors analyze by using the idiosyncratic concept of leaders in the foreign policy output adopted by a country.. The findings in this research indicate that there is an influence of Matteo Salvini's perception and personality which has an impact on the foreign policy adopted by Italy in 2018. Aggressive foreign policy and excluding international law from the 1951 Refugee Convention and the Common European Asylum System (CEAS) regarding migrant issues is an indication of the perception elite in breaking through political boundaries. His high level of nationalism and ability to control events and be actively involved in policy making allows Salvini to act dominantly and tends to delegate less power to maintain his power through the anti-refugee terms promoted by Salvini.